Fault Tolerant Coverage and Connectivity in Presence of Channel Randomness - Anil Kumar Sagar; D. K. Lobiyal (The Scientific World Journal)
Some applications of wireless sensor network require K-coverage and K-connectivity to ensure the system to be fault tolerance and to make it more reliable. Therefore, it makes coverage and connectivity an important issue in wireless sensor networks. In this paper, we proposed K-coverage and K-connectivity models for wireless sensor networks. In both models, nodes are distributed according to Poisson distribution in the sensor field. To make the proposed model more realistic we used log-normal shadowing path loss model to capture the radio irregularities and studied its impact on K-coverage and K-connectivity. The value of K can be different for different types of applications. Further, we also analyzed the problem of node failure for K-coverage model. In the simulation section, results clearly show that coverage and connectivity of wireless sensor network depend on the node density, shadowing parameters like the path loss exponent, and standard deviation.